COLONIAL INTERVENTION IN WATER MANAGEMENT: THE CASE STUDY OF DELHI - Ms Anchal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In history, wherever the British government established its supremacy, there was a huge change in the ecology due to their policies. Changes in the environment, whether voluntary or involuntary, happened due to their policies. This change in the environment happened slowly, but its effect was felt immediately by the local people. Delhi was under the British Empire from 1803 to 1947 and during this period the ecology of Delhi also changed a lot. Initially, from 1815 to 1911, Delhi went through various ecological changes, after 1912 there was a rapid change in the ecology of Delhi. Delhi's forests, gardens and natural water sources were exhausted very quickly.